Study of the Microstructure and Fracture Toughness of TC17 Titanium Alloy Linear Friction Welding Joint - Xiaohong Li (Metals, 2019)
In this paper, the fracture toughness of the thermo-mechanically affected zone (TMAZ) and the weld zone (WZ) of the TC17 titanium alloy linear friction welding joint was studied. The relationship between microstructure and fracture toughness of the joint, as well as the morphologies of the joint microstructure and fracture were investigated. The results indicate that after heat treatment, there was no significant difference in hardness between the WZ and the TMAZ of the joint, which was about 420 HV. However, the microstructures of the different zones of the joint were significantly different. The TMAZ was composed of coarse grains having an internal basket-shaped α phase with an uneven grain size, while the WZ was composed of relatively uniform fine grains and contained a sheet-like α phase. The fracture toughness of the TMAZ was found to be higher than that of the WZ, indicating that the microstructure of the joint had a significant impact on the fracture toughness. In addition, the fracture resistance of the TMAZ with coarser grains and uneven microstructure was better than that of the WZ with fine grains and uniform microstructure.